DINAMIKA POLA PIKIR ORANG JAWA DI TENGAH ARUS MODERNISASI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Yogyakarta is regarded as one of the center of Javanese culture, but the mindset of the people of Yogyakarta nowadays has remarkably changed from the general image of Javanese community. This dynamics could not be separated from the development of modern educational institutions which have been disseminating rationalism that gradually shifts mysticism as the basis of ideology and culture. Nevertheless. the remnants of Javanese beliefs are still seen in some traditional rituals that mostly have lost much of their ideologicalsignificance.Suchculturalcredosalso often reappearwhen rationality is unable to offer a definitive answer to a problem. Keywords: change of mindset. mysticism. rationality. Yogyakarta. Java